Analisis Strategi Pemasaran Dalam Memasuki Pemasaran Global (Studi Kasus : MS Glow) - Ridho Fachrozie; Elsa Zulfita; Minta Ito Lubis; Siti Hazrah; Suhairi Suhairi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Skincare MS Glow has been successfully recognized by the people of the country. MS Glow has also succeeded in expanding its market by having agents and official members throughout Indonesia and abroad. Not only that, MS Glow has succeeded in presenting a beauty clinic so that its customers can do skin care with experts in their fields. Until now, MS Glow's skincare business continues to strengthen its marketing strategy so that it can continue to survive in the beauty industry. In achieving success can not be separated from the ability to read opportunities and take advantage of the momentum. Then create innovations to answer anxiety and desire in developing societies. The marketing strategy implemented by MS Glow includes promotions through advertisements. In this study, the authors used qualitative research methods, critical discussion of the author's point of view, as well as support for literature searches, citations, expert opinions, and previous findings on the subject. Sources of data obtained by researchers are not only basic data obtained from previous studies. Based on the results of research through observations that have been carried out through internet media sources and direct interviews with several MS GLOW branch managers in Medan City, there are several marketing strategies used by MS GLOW to be able to face global marketing.